Producción audiovisual del mediometraje Cinema Express - Leyva Sukata, Renzo Jesus (2023)
The following report critically describes the process of making the medium-length film Cinema Express, premiered in 2019 at the Film Week Festival of the University of Lima. The different stages of production are developed and a concise analysis of the successes and errors that occurred in the process, in addition to the recognitions achieved. The objective is to make known what the production of a low cost film work in Peru currently entails and the reasoning of the agents involved in the production, emphasizing the director's vision.